2018
DOI: 10.29317/ejpfm.2018020302
|View full text |Cite
|
Sign up to set email alerts
|

Magnetron deposition of yttria-stabilised zirconia electrolyte for solid oxide fuel cells

Abstract: The aim of the article is to review the latest achievements in the field of magnetron deposition of thinfilm yttria-stabilised zirconia (YSZ) electrolyte for solid oxide fuel cells (SOFC). The main attention is paid to the use of magnetron sputtering for formation of YSZ electrolyte up to 10 µm thick on the anode substrates of intermediate-temperature SOFCs operating at a temperature of (600 − 800) • C . The influence of the types of power sources and such deposition parameters as substrate temperature, substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The magnetron sputtered YSZ electrolyte films were studied in [ 14 , 15 , 16 , 17 , 18 ] and in the state-of-the-art paper [ 19 ]. It was shown that the microstructure, phase composition, and other parameters of the YSZ electrolyte films depended on the magnetron sputtering modes, electric supply parameters (RF, DC, pulsed DC), working pressure, substrate temperature, substrate bias voltage, and post-annealing treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetron sputtered YSZ electrolyte films were studied in [ 14 , 15 , 16 , 17 , 18 ] and in the state-of-the-art paper [ 19 ]. It was shown that the microstructure, phase composition, and other parameters of the YSZ electrolyte films depended on the magnetron sputtering modes, electric supply parameters (RF, DC, pulsed DC), working pressure, substrate temperature, substrate bias voltage, and post-annealing treatment.…”
Section: Introductionmentioning
confidence: 99%
“…It has been clearly known that reducing the thickness of the electrolyte from hundreds of micrometers to several micrometers allows the operating temperature to be reduced from 900-1000 °C to 650-800 °C [23]. Although traditional well-studied preparation methods of electrolytes, such as slip casting, screen printing, electrophoretic deposition, plasma spraying, etc., have relative simplicity and low cost, they are not suitable for preparing electrolyte thin films [24]. As a thin-film deposition technique, physical vapour deposition (PVD) is known for its high reliability and reproducibility.…”
Section: Introductionmentioning
confidence: 99%